FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PENJUALAN SPAREPART PADA PT. CALISPO MULTI UTAMA MEDAN - Muhammad Yamin Siregar; Winita Winita (Universitas Medan Area, 2017)
This study aims to determine whether there is influence between advertising and personal selling to volume of spare parts sales at PT. Calispo Multi UtamaMedan. The population in this study is the buyers who make repeat purchases. Where 7.5% of the buyers population who make repeat purchases as sample for this study is 74 people. Thedata collected by using a questionnaire distributed to the buyer where the question regarding the indicators of advertising, personal selling and sales volume of spare parts at PT. Calispo Multi Utama Medan. The analytical method used is descriptive and statistical analysis method that uses linear multiple regression analysis, significant Tests And Testing simultaneous partial significant. The execution method of data analysis using SPSS 19.0 for Windows . The data used is primary and secondary data . This research using 74 respondents in the sample Participants were drawn by accidental sampling . Results based on multiple linear regression analysis showed that the variables advertising and significant positive effect Against sales volume of spare parts at PT. Calispo Multi Utama Medan.Keywords: Advertising, Personal Selling,Sales Volume of spare parts